STRATEGI KEPALA MADRASAH DALAM PENGELOLAAN KURIKULUM BERBASIS LITERASI DI MAN 5 JOMBANG - Reda Reda; Lukman Hakim (Jurnal Manajemen Pendidikan, 2026)
This study analyzes the madrasah head’s strategy in literacy-based curriculum management at MAN 5 Jombang across four managerial dimensions: planning, implementation, evaluation, and obstacle resolution. Unlike prior studies that view literacy as a habituation program, this research positions literacy as an integral component of strategic curriculum leadership. Methods: A qualitative descriptive approach was employed. Data were gathered through in-depth interviews, participatory observation, and documentation from six purposively selected informants—the madrasah head, vice principal for curriculum, librarian teacher, two literacy teachers, and one student member of the Literacy Working Group—conducted from January to March 2026. Data analysis used Miles, Huberman, and Saldaña’s interactive model, validated through source and technique triangulation. Results: Planning integrated literacy into the Madrasah Work Plan through participatory staff meetings and established a Literacy Working Group with measurable targets. Implementation encompassed reading habituation, reading corners, periodic student publications, journalism training with external media partners, and digital media use. Evaluation applied product-based indicators monitored through periodic reviews. Obstacle resolution relied on motivational leadership, public recognition, principal exemplary conduct, and technology regulation. Novelty: This study demonstrates that sustainable literacy competence demands systematic, cross-disciplinary curriculum management strategies underpinned by consistent principal leadership.